LEGAL PROTECTION FOR TOURIST SECURITY AND SAFETY AT THE INTERNATIONAL SURFING COMPETITION EVENT FROM THE MAQASHID SYARIAH PERSPECTIVE (CASE STUDY OF AFULU VILLAGE, AFULU DISTRICT, NORTH NIAS REGENCY) - Astrid Maulidatun Rahmah; Cahaya Permata (Journal Analytica Islamica, 2025)
The tourism industry is a prospective commodity that is considered to have an important role in national development, but tourist attractions can also pose a risk of danger to tourists, therefore to support safety and security at tourist destinations, Law Number 10 of 2009 concerning tourism and Law Number 8 of 1999 concerning consumer protection have been enacted in order to guarantee and provide security and safety for tourists. This study aims to determine the form of security facilities available at the international surfing event held in Afulu District, North Nias, and what form of protection concept is based on the Maqashid Syariah perspective. The type of research is empirical legal research with a living case studies approach, statute approach and conceptual approach. The results of this study indicate that the facilities at the international surfing event held in North Nias have not met the safety and security aspects such as the lack of a monitoring tower, a place to store goods, a route to tourist attractions, the provision of clinics or First Aid for Accidents (P3K) permanently. So, based on the perspective of Maqashid Syariah, especially from the concept of hifz al-nafs (protecting the soul) and hifz al-mal (protecting property), the organizers of the International Surfing Event should coordinate with the beach tourism managers and must provide security and safety facilities in accordance with applicable laws and regulations.